International New Venture: Top Glove Corporation Bhd. - Suraya Hanim, Zainul (2009)
Internationalization is no longer a choice but is a necessity that alloms growth and survival expansion. This study is meant to be both descriptive and explanatory study which aims to assess the environment of internationalization in international new venture(INV)context of a specific Malaysian company, namely Top Glove Corporation Bhd. by looking to the drivers that enable the company in expanding their activities and operations abroad. The findings show the importance extensive assistance of the governmental institutions through the establishment of multiple plans, schemes, initiatives and incentives